Pilot study of the vertical variations in outdoor pollutant concentrations and environmental conditions along the height of a tall building. (15th June 2018) - Azimi, Parham; Zhao, Haoran; Fazli, Torkan; Zhao, Dan; Faramarzi, Afshin; Leung, Luke; Stephens, Brent
Abstract: It is generally assumed that vertical pollutant dispersion can reduce exposures to ambient pollutants in tall buildings, as concentrations of some ground-source pollutants are diluted at higher floors. However, we are aware of very few measurements of airborne pollutant concentrations that have been made specifically along the height of tall buildings. Therefore, we conducted a pilot study to measure the vertical variation in the concentrations of several outdoor pollutants and environmental parameters along the height of a ∼60-story (∼300 m) building in downtown Chicago, IL during a one-week period in the summer of 2017. Simultaneous measurements of concentrations of size-resolved particulate matter 0.3–10 μm (which were also used to estimate PM1, PM2.5, and PM10 mass concentrations), ozone (O3 ), nitrogen dioxide (NO2 ), carbon dioxide (CO2 ), and carbon monoxide (CO), as well as temperature and relative humidity, were made using multiple sets of instrumentation installed in the outdoor air intakes of the mechanical systems upstream of any filtration or mixing processes on the 2nd, 16th, 29th, and 44th floors and in an open-air area on the 61st floor. The average PM1 and PM2.5 concentrations estimated on the top two floors were more than 30% lower than on the 2nd floor. Temperature, humidity ratio, and CO2 concentrations decreased with height, O3 concentrations increased with height, and NO2 concentrations were less consistent. Most of the differences between floors were statistically significant. Floor height was more strongly correlated with PM1, PM2.5, PM10, CO2, and O3 concentrations than with local wind speed and direction. Graphical abstract: Image 1 Highlights: Measured the vertical variation of outdoor pollutant concentrations along a tall building. Air temperature, humidity, PM1, PM2.5, PM10, and CO2 decreased with building height. Ozone generally increased with building height and NO2 was less consistent. Floor height was more strongly correlated with PM, CO2, and O3 concentrations than with local wind speed and direction.